TECHNOLOGY-MEDIATED INSTRUCTION IN TRAINING TRANSFER: A SYSTEMATIC REVIEW - Shoib, Abdul Rashid; Ismail, Ismi Arif; Abd Aziz, Mohd Faiq; Samad, Norlela (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
The transfer of training remains a critical challenge in achieving effective learning outcomes, particularly within technology-mediated environments. While extensive research has examined trainee characteristics, training design, and work environment as key factors of training transfer, the mediating role of Technology-Mediated Instruction (TMI) has received comparatively limited attention. This systematic literature review (SLR) seeks to examine and consolidate existing research on the mediating influence of TMI in enhancing training transfer outcomes. To address this research gap, the review adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, ensuring a methodologically sound and transparent approach. A thorough search was conducted in two prominent academic databases, Scopus and Web of Science (WoS), resulting in the identification of 28 primary studies that met the inclusion criteria. The analysis of these studies led to the emergence of three key thematic areas: (1) Innovative Pedagogies and Learning Transfer, highlighting the role of learner-centred and active learning approaches in promoting transfer; (2) Artificial Intelligence, Digital Technologies, and Instructional Tools, focusing on how emerging technologies and digital platforms facilitate engagement and retention; and (3) Teacher Development, Competencies, and Educational Contexts, emphasising the importance of trainer skills and contextual factors in maximising the effectiveness of technology-mediated delivery. The findings suggest that TMI serves as a critical enabler, connecting instructional strategies, digital tools, and human competencies to training transfer outcomes. This review contributes to advancing the theoretical understanding of TMI as a mediator and offers practical insights for designing more effective digital training interventions. The study concludes by highlighting future research directions, including the need for empirical validation of TMI’s mediating effects across different organisational and cultural contexts.